PENGARUH PEMBELAJARAN KEWIRAUSAHAAN DAN BIMBINGAN KARIR TERHADAP MINAT BERWIRAUSAHA MAHASISWA PENDIDIKAN EKONOMI DI UNIVERSITAS SEBELAS MARET PADA ERA MASYARAKAT EKONOMI ASEAN (MEA) - -, Ulfa Lufiana -; -, Trisno Martono Indriayu; -, Sudarno - (Pendidikan Ekonomi Bidang Keahlian Khusus Tata Niaga FKIP Universitas Sebelas Maret, 2018)
This research was conducted to find out whether or not: (1) the influence of Entrepreneurship learning on entrepreneurial interest in FKIP students in the program of Economic Education at Sebelas Maret University Surakarta in the AEC era, (2) the effect of Career Guidance learning on entrepreneurship interest in FKIP students in the program of Economic Education Sebelas Maret University Surakarta in the AEC era, and (3) the influence of Entrepreneurship learning and Career Guidance on entrepreneurial interest in FKIP students in the program of Economic Education at Sebelas Maret University Surakarta in the AEC era. This research was using quantitative research with descriptive research. The population in this research were all economic students of the 2014 Sebelas Maret University in Surakarta as many as 57 students. Technique of collecting data used was questionnaire. Questionnaires techniqu are used to collect data about Entrepreneurship learning, Career Guidance learning, and entrepreneurial interests at AEC era. Data analysis used in this study is multiple linear regression analysis with level of significance 0,05.The results of this research can be concluded that: (1) there was a positive and significant influence of entrepreneurship learning on entrepreneurial interest in economic education students in the era of the ASEAN Economic Community (AEC) with partial contribution value 37.33%, (2) there was a positive and significant influence of Career Guidance learning on entrepreneurial interest in economic education students in the era of the ASEAN Economic Community (AEC) with partial contribution value 11.49%, and (3) there is a positive and significant influence of entrepreneurship learning and Career Guidance learning on entrepreneurial interest Economic education students in the era of the ASEAN Economic Community (AEC) with simultaneous contribution 43.5%.